Alasan mengapa penderita hipertensi masih merokok aktif : studi fenomenologi - Sri Mumpuni Yuniarsih; Tri Asih Wulandari; Rusdi; Siwi Sri Widhowati (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: Hypertension is a disease with a high prevalence. Smoking is one of the factors that cause hypertension, even though there are still many people with hypertension who smoke and even become heavy smokers. We need to know the reasons why people with hypertension become active smokers.Objective: This research was conducted to find out the reasons for hypertensive patients who remain active smokers.Method: The research method used is qualitative research with a phenomenological approach. The 6 (six) subjects were interviewed face to face with an interview guide. The research results were analyzed using thematic analysis techniques.Results: The results of the study found 5 themes about why people with hypertension are still active smokers. The five are lack of knowledge, addiction, habits, environment and economic conditions. QConclusion: Based on the theme obtained, it can be concluded that hypertension sufferers have low knowledge about hypertension so they are still active smokers